ESTIMATION OF FERRITIN IN VEGETARIAN AND NON-VEGETARIAN FEMALE MEDICAL COLLEGE STUDENTS - BHARTIYA, JAI PRAKASH; CHAUDHARY, VIJAY; SINGH, ALKA; KATHARIYA, GOBARDHAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Iron stores in the body exist primarily in the form of ferritin. Iron deficiency anemia is the state where iron level is below normal, low transferrin saturation and ferritin as well as high iron binding capacity. National Family Health Survey-3 shows the prevalence of anemia in 56.2% of women of 15–49 year, 79.2% among children aged 6–35 months, 57.9% in pregnant women. Methods: 50 (apparently healthy female students of the medical college) were included in the study. Ferritin level was estimated by Advia Centaur XP Immunoassay System. Results: About 50% of non-vegetarian and about 79% of vegetarian were anemic. Ferritin level among non-vegetarians was significantly higher than vegetarians. Discussion: Although vegetarian lifestyle has great advantages, vegetarians do have a high risk of a deficiency of some nutrients, including iron. The most readily absorbed type of iron is hemiron which comes from meat, poultry, and fish. Furthermore, plant foods contain several iron-absorption inhibitors. Getting enough iron from non-hemiron sources can be a challenge. Iron requirements for vegetarians are about 1.8 times higher, compared to non-vegetarians. Conclusion: This form of malnutrition is most common and one of the leading causes of disease among girls and women in developing countries. Knowing about ferritin level will help understand iron status and thus avoiding the disease.